2010
DOI: 10.1016/j.immuni.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The Long and Winding Road to Understanding and Conquering Type 1 Diabetes

Abstract: Autoimmune diseases with high population prevalence such as type 1 diabetes (T1D) develop as a result of ill-defined interactions between putative environmental triggers and a constellation of genetic elements scattered throughout the genome. In T1D, these interactions somehow trigger a loss of tolerance to pancreatic beta cells, manifested in the form of a chronic autoimmune response that mobilizes virtually every cell type of the immune system and progressively erodes the host's beta cell mass. The five acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 103 publications
0
64
0
Order By: Relevance
“…The islet autoreactive CD4 + helper T (T H ) cells and CD8 + cytotoxic T (T C ) cells are involved in the immune pathogenesis of human T1D and NOD mice (19)(20)(21)(22)(23)(24)(25). Recently we showed that IL-7 can promote the development of IFN-γ-producing T H 1 cells, but not IL-17-producing T H 17 cells, from the naïve T cells of humans and of the C57BL/6 mice (26).…”
mentioning
confidence: 99%
“…The islet autoreactive CD4 + helper T (T H ) cells and CD8 + cytotoxic T (T C ) cells are involved in the immune pathogenesis of human T1D and NOD mice (19)(20)(21)(22)(23)(24)(25). Recently we showed that IL-7 can promote the development of IFN-γ-producing T H 1 cells, but not IL-17-producing T H 17 cells, from the naïve T cells of humans and of the C57BL/6 mice (26).…”
mentioning
confidence: 99%
“…3B-D, G and 4B-D), consistent with the report of Ekland et al [27], showing that exclusion from FO areas is not a prerequisite for competitive elimination. Nevertheless, the observation led us to speculate that NOD HEL-specific B lymphocytes were better positioned to receive T-cell help; especially in mice on a genetic background where self-tolerance in the T-cell compartment is known to be defective, resulting in the presence of autoreactive T cells capable of providing help [28]. Consistent with this hypothesis, the second difference between self-reactive B lymphocytes on NOD and B6 backgrounds was the enhanced susceptibility of the former to loss of anergy following provision of help (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Type-1 diabetes (T1D) in both humans and nonobese diabetic (NOD) mice is caused by a chronic, T-cell-dependent autoCorrespondence: Dr. Pere Santamaria e-mail: psantama@ucalgary.ca immune response against insulin-producing pancreatic β cells [1] in which CD8 + cells play a critical role (reviewed in [2]). A relatively large fraction of islet-associated CD8 + cells in NOD mice use highly homologous TCR-α chains and recognize an epitope * These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%